Atypical presentation of Neisseria meningitidis serogroup W disease is associated with the introduction of the 2013 strain. (29th April 2021) - Säll, Olof; Stenmark, Bianca; Jacobsson, Susanne; Eriksson, Lorraine; Thulin Hedberg, Sara; Hertting, Olof; Fredlund, Hans; Sundqvist, Martin; Mölling, Paula
Abstract: Since 2015, the incidence of invasive meningococcal disease (IMD) caused by serogroup W (MenW) has increased in Sweden, due to the introduction of the 2013 strain belonging to clonal complex 11. The aim of this study was to describe the clinical presentation of MenW infections, in particular the 2013 strain, including genetic associations. Medical records of confirmed MenW IMD cases in Sweden during the years 1995–2019 ( n = 113) were retrospectively reviewed and the clinical data analysed according to strain. Of all MenW patients, bacteraemia without the focus of infection was seen in 44%, bacteraemic pneumonia in 26%, meningitis in 13% and epiglottitis in 8%, gastrointestinal symptoms in 48% and 4% presented with petechiae. Phylogenetic analysis was used for possible links between genetic relationship and clinical picture. The 2013 strain infections, particularly in one cluster, were associated with more severe disease compared with other MenW infections. The patients with 2013 strain infections ( n = 68) were older (52 years vs . 25 years for other strains), presented more often with diarrhoea as an atypical presentation ( P = 0.045) and were more frequently admitted for intensive care ( P = 0.032). There is a risk that the atypical clinical presentation of MenW infections, with predominantly gastrointestinal or respiratory symptoms rather than neck stiffness or petechiae, may lead to delay in life-saving treatment.